C Cost Minimization Analysis (CMA) Penggunaan Obat Amlodipine Dan Captopril Pada Pasien Hipertensi di RSUD Sultan Suriansyah Banjarmasin - Azizah, Siti; Yuwindry, Iwan; Ikeh, Tri Sulapmi D.; Melviani, Melviani (Jurnal Pelayanan Kefarmasian dan Sains, 2024)
Background: Hypertension is one of the serious problems currently known as the silent killer, and the prevalence throughout the world of hypertension is very high, which has the potential to increase the medical costs that must be borne by patients, therefore minimal treatment of hypertension can reduce the high incidence of hypertension.Objective: The aim of this study was to determine the most cost-minimum costs of using the drugs amlodipine and captopril in hypertensive patients in the outpatient installation of Sultan Suriansyah Hospital, Banjarmasin.Methods: This research was conducted using an observational analytical method with a cross sectional design. Data collection was carried out using medical records and details of drug costs in the pharmacy department, and receipts in the finance department for hypertensive patients in outpatient installations who received amlodipine and captopril treatment at Sultan Suriansyah Hospital, Banjarmasin. The sample used was 38 patients. The cost components collected are direct medical costs including the total costs for antihypertensive treatment, costs for treating comorbidities, administration costs and consultation costs.Results: The results of this research showed that the average total direct medical costs for the amlodipine group were Rp.98.491 and the captopril group was Rp.109.613.Conclusion: Based on cost minimization analysis calculations, the 2 antihypertensive drug therapies that are cost minimized are amlodipine 10 mg tablets compared to captopril 25 mg tablets.